(untitled) (Fiep Bulletin - online, 2015)
This descriptive study aims to verify what would be the reaction of teenagers while in competitive sports situations. In order to collect samples, we have used the GONÇALVES’ (1988) questionnaire, with the adaptation from LOPES (1994). The sample has involved 1754 teenagers from 14 to 18 years old, 1055 were male (60.1%) and 699 were female (39.9%). The results indicates that female are more likely to show off attitudes according to the concept of sportive spirit than the male, whereas due to the behavior they would have in a competitive situation tend to exist a balance between both genders.